Methyl aminolevulinate daylight photodynamic therapy applied at home for non‐hyperkeratotic actinic keratosis of the face or scalp: an open, interventional study conducted in Germany. (22nd February 2019) - Karrer, S.; Aschoff, R.A.G.; Dominicus, R.; Krähn‐Senftleben, G.; Gauglitz, G.G.; Zarzour, A.; Kerrouche, N.; Chavda, R.; Szeimies, R.‐M.
Abstract: Background: The efficacy and safety of methyl aminolevulinate daylight photodynamic therapy (MAL DL‐PDT) for actinic keratosis (AK) treatment has previously been demonstrated in several studies. Objective: To evaluate patient‐reported outcomes, effectiveness and tolerability of patient self‐applied MAL DL‐PDT. Patients and methods: An open study was conducted in Germany in patients with thin or non‐hyperkeratotic and non‐pigmented AK. At baseline, the investigator delimited the target anatomical area and skin preparation was discretionary. On day 1, the patient performed MAL DL‐PDT at home, in accordance with instructions (after applying sunscreen and skin preparation by abrasive pad). Patient questionnaires were completed on day 1 and 3 months post‐treatment. Effectiveness was assessed by investigator at 3 months. Pain and adverse events (AE) were recorded. Results: Patients (n = 50) were mostly elderly (mean age: 73.4 years) men (86%). After treatment on day 1, 94% of patients were overall satisfied or very satisfied with the treatment and 98% found the instructions convenient. At 3 months, most patients were satisfied or very satisfied with treatment effectiveness (88%) and aspect of their skin (80%). At 3 months, 62% of overall lesions were completely clear. The main related AEs were mild and expected (erythema, procedural pain and skin burning sensation). Conclusions: Patient self‐application of MAL DL‐PDT resulted in high levels of patient satisfaction, effectiveness and tolerability. Abstract : Linked article: This article is commented on E. Ramelyte et al ., p. 629 in this issue. To view this article visithttps://doi.org/10.1111/jdv.15535 .